Neighborhood near Santa Clara on El Camino Real - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Panoramic view of a restaurant named the "Fatted Calf" and a neighborhood adjacent to El Camino Real. A street sign on the right of the image indicates the location of the photograph is close to Mission Santa Clara and about two miles from the city of Santa Clara. An additional sign below indicates the relative distance of several communities from the site of the photograph. Los Gatos is 10 miles away, Santa Cruz is 35 miles away, Saratoga is 9 miles, and Big Basin is 31 miles.